Does Age Matter for Innovative Behavior? A Mediated Moderation Model of Organizational Justice, Creative Self-Efficacy, and Innovative Behavior Among IT Professionals - Ahmad Qammar; Muhammad Shakeel Aslam; Sadeeqa Riaz Khan; Nasira Jabeen; Melkamu Deressa Amentie (Human Behavior and Emerging Technologies)
The significance of innovation and the expectation for employees to exhibit innovative behavior have been heightened as a result of swift technological advancements and an evolving business landscape. The present research is aimed at examining the impact of organizational justice on fostering innovation in a dynamic business environment. Extending the previous literature which generally examined the combined impact of different facets of organizational justice, we employed the social cognitive theory framework to investigate the mechanism through which the three facets of organizational justice (distributive justice, procedural justice, and interactional justice) lead to employee innovative behavior through the mediating role of employees’ creative self-efficacy. Additionally, we examined the role of age as a pertinent boundary condition, an aspect often overlooked in the literature on creative self-efficacy and innovative behavior which is likely to augment our understanding of the potential mechanism driving innovative behavior. The sample comprises 320 individuals employed in the information technology industry. The data were collected in two waves, and subsequent analysis was conducted utilizing the Warp PLS 8 software. The present investigation employed partial least square (PLS)-based structural equation modeling (SEM) to conduct analysis and evaluate hypotheses. The results indicate that all three facets of organizational justice have a positive influence on employees’ creative self-efficacy, which subsequently manifests in their innovative behavior. Additionally, age has an impact on the relationship between creative self-efficacy and employee innovative behavior, which becomes less pronounced as employees get older. Theoretical contributions and practical implications for practitioners are discussed.